Perancangan User Experience Aplikasi Hospitality Menggunakan Metode Human Centered Design - M. Wava Ferdianyah Putra; Dike Bayu Magfira; Firman Yudianto; Teguh Herlambang; Airlangga Bhumintara Amitaba; Nicko Satria Utama (JURNAL TECNOSCIENZA, 2026)
The development of digital applications in the hospitality sector demands the design of user experiences that can clearly represent interaction flows. However, Boksem Technology does not yet have a structured User Experience (UX) design for hospitality applications based on Artificial Intelligence and blockchain. This study is a preliminary investigation aimed at designing the application’s UX through the development of mid-fidelity wireframes. The research method employed is descriptive qualitative with a Human Centered Design (HCD) approach. Data were collected through literature review, analysis of public reviews, and requirement elicitation with the company owner. The results of this study produce mid-fidelity wireframe designs that include the visualization of an AIbased intelligent travel assistant workflow and the integration of a dual payment gateway (bank and crypto). This design provides a modular information architecture that has been validated by stakeholders as an operational blueprint for further interface development. These findings bridge the gap between complex business ideation and early technical implementation in the hospitality industry.